Navigating Multinational Communication Barriers Through Cultural Insight and Technological Adaptation for Organizational Cohesion - Al Hakim, Yusuf Rahman; Sigita, Dwi Sembe (Metromedia, 2025)
This literature-based analysis explores the communication challenges encountered by multinational organizations and the strategies employed to address them. The study focuses on three core dimensions that influence organizational communication: cultural diversity, language barriers, and technological disparity. Drawing upon established theoretical frameworks and empirical research, the discussion outlines how these variables affect interpersonal dynamics, team performance, and institutional coordination. Intercultural misalignment can disrupt understanding, while language proficiency gaps hinder participation and inclusivity. Likewise, inconsistencies in communication tools and infrastructure contribute to fragmented workflows. The findings emphasize that effective navigation of these variables requires a multi-layered approach that integrates cultural intelligence, multilingual competence, and technological accessibility. Leaders who champion inclusive communication practices and institutional structures that support transparency and feedback are instrumental in mitigating these challenges. The literature underscores the importance of designing communication systems that are not only operationally efficient but also socially equitable. In doing so, organizations can enhance their capacity to function cohesively across borders and cultures, enabling them to remain competitive and adaptive in increasingly interconnected environments.